Relative Frequency of Blood-Borne Viruses in Hemodialysis-Dependent and Kidney Transplant Recipients in Iran - Fatemeh HATATIAN; Farzad BABAKHANI; Hoda GUDARZI; Navid MOMENIFAR; Mehdi NOROUZI; Mina SHAFIEIFAR; Ehsan KAKAVANDI; Ahmadreza SADEGHI; Hedyeh SHARBATDAR-ALAEI; Mohammad FARAHMAND; Maedeh AMIRI-ROUDY; Hamid Reza JAHANTIGH; et al. (Tehran University of Medical Sciences, 2020)
Background: Hemodialysis (HD) patients and kidney transplant (KT) recipients are exposed to be infected by blood-borne viruses (BBVs). Current study was conducted to evaluate the prevalence of BBVs in HD and KT patients in the whole Iranian population. Methods: From Jan 2016 to Dec 2017, 174 hemodialysis and 139 kidney transplant recipients enrolled in this survey. After blood sampling, serum samples were detected for HBV, HCV, HCMV, HIV and HTLV antibodies. Seropositive samples confirmed by Polymerase chain reaction (PCR) method. Results: Overall, 6 (3.44%) and 3 (2.15%) of hemodialysis-dependent and transplantation patients had evidence of HCV infection, whereas no patients were HIV and HBV positive, two cases (1.14%) of hemodialysis and one case (0.71%) of transplantation patients demonstrated the HTLV-1 infection. 52 (37.4%) of patients received graft were positive for HCMV antibody. In addition, our study showed a co-infection of HCMV with HCV (3 patients, 2.15%) in transplantation patients. Conclusion: Prevalence of BBVs infection was lower in comparison to the previous studies. The current strict infection control practices in Iran appear to be effective in limiting dialysis and related infections after transplantation. Because BBVs infections constantly occur especially in dialysis and after transplantation units, our data will be useful to build a new strategic plan for the elimination of BBVs infection in kidney therapycenters.